New Method for the Deposition of Nickel Oxide in Porous Scaffolds for Electrodes in Solid Oxide Fuel Cells and Electrolyzers. Issue 1 (14th October 2016) - Ruiz‐Trejo, Enrique; Puolamaa, Milla; Sum, Brian; Tariq, Farid; Yufit, Vladimir; Brandon, Nigel P.
Abstract: A simple chemical bath deposition is used to coat a complex porous ceramic scaffold with a conformal Ni layer. The resulting composite is used as a solid oxide fuel cell electrode, and its electrochemical response is measured in humidified hydrogen. X‐ray tomography is used to determine the microstructural characteristics of the uncoated and Ni‐coated porous structure, which include the surface area to total volume, the radial pore size, and the size of the necks between the pores. Abstract : Bathing beauty : An alternative method for the fabrication of anodes for solid oxide fuel cells is presented. Ni is incorporated into a porous scaffold and tested as an anode. X‐ray tomography is used to compare the uncoated and Ni‐coated scaffolds.